‘Good Reading Among Young Canadians’ (c. 1900–50): The Canadian Association of Children’s Librarians, Young Canada’s Book Week, and the Persistence of Professional Discourse - Edwards, Gail (Library & information history, 2012)
Claims by children’s librarians to specialized knowledge about children’s literature developed in parallel to the profession. Successive generations of children’s librarians argued that children’s library services played a vital role in children’s moral, intellectual, and civic education. At the same time, they negotiated gendered relations of power as they struggled to gain professional recognition. In Canada, the selection policies, collection development practices, and models for programming developed at Boys and Girls House at the Toronto Public Library during Lillian H. Smith’s forty-year career as the Head of the Boys and Girls Division were disseminated through professional education, workshops, and programmes, publications, and networks of librarians who had worked at the Toronto Public Library. The idea of enduring standards of evaluation was central to their understanding of the circulation of texts, and to their own expert claims. In 1949, the Canadian Association of Children’s Librarians, as a division of the Canadian Library Association, established Young Canada’s Book Week to promote good reading, reinforce Anglo-Canadian civic values, and construct a common literary culture for Canadian children. The annual celebration became the subject of vigorous debate about the relationship between children’s popular culture and good reading and the role of librarians in mediating the relationship between children and books.